Beyond Islamic Legal Principle: Social Justification of Adolescent Forced Marriage after Sexual Intercourse - Masruroh, Ainul; Mahmutarom, Mahmutarom; Kumar, Abhishek; Afiyah, Siti (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The social justification for the practice of forced marriage among adolescents engaged in premarital sexual activity reveals a clear contradiction between prevailing social norms and the principles of Islamic law. However, this phenomenon tends to be overlooked in previous studies. In addition to responding to the shortcomings of existing studies, this study also aims to explain the characteristics of forced marriage practices for adolescents who engage in sexual activity outside of marriage. This research is a descriptive qualitative study that uses a case study approach. The findings indicate that forced marriage among adolescents is frequently employed as a means of safeguarding both individual and familial honor within the prevailing social value system of the community. There are three main findings that support this conclusion. First, the decision to arrange a forced marriage is usually made by the family without considering the teenager's personal wishes. Second, the reason this practice is accepted by the community is because it is believed to uphold shared moral values and standards of proper behavior. Third, the controversies that arise reflect the contradictions between the social system and the principles of Islamic law. The significance of this study rests in its contribution to enriching the discourse of Islamic law through a social reality-based approach, thereby creating space for contextual reinterpretation of the law with an emphasis on the welfare of its subjects.